2020
DOI: 10.7554/elife.60648
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of a mycobacterial cell-surface lipid into host epithelial membranes promotes infectivity

Abstract: Several virulence lipids populate the outer cell wall of pathogenic mycobacteria (Jackson, 2014). Phthiocerol dimycocerosate (PDIM), one of the most abundant outer membrane lipids (Anderson, 1929), plays important roles in both defending against host antimicrobial programs (Camacho et al., 2001; Cox et al., 1999; Murry et al., 2009) and in evading these programs altogether (Cambier et al., 2014a; Rousseau et al., 2004). Immediately following infection, mycobacteria rely on PDIM to evade Myd88-dependent recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 65 publications
2
39
0
Order By: Relevance
“…In that model, epithelial cells are infected in the first 48 h after infection; however, M. tuberculosis does not appear to replicate or persist in these cells 7 . The mycobacterial lipid phthiocerol dimycocerosate (PDIM) can spread into epithelial membranes and modulate immune responses 16 . Microfold cells (M cells) may also be a portal of entry, allowing M. tuberculosis to gain access to underlying lymphoid tissue in the upper airways 17 , 18 .…”
Section: How M Tuberculosis Establishes Infectionmentioning
confidence: 99%
“…In that model, epithelial cells are infected in the first 48 h after infection; however, M. tuberculosis does not appear to replicate or persist in these cells 7 . The mycobacterial lipid phthiocerol dimycocerosate (PDIM) can spread into epithelial membranes and modulate immune responses 16 . Microfold cells (M cells) may also be a portal of entry, allowing M. tuberculosis to gain access to underlying lymphoid tissue in the upper airways 17 , 18 .…”
Section: How M Tuberculosis Establishes Infectionmentioning
confidence: 99%
“…However, we have not yet shown whether the mitochondrial damage is through ESAT-6 or some other ESX-1 substrate. Similarly, we and others have shown that PDIM facilitates ESAT-6 mediated phagosomal damage, possibly by changing the characteristics of the mycobacterial surface, host membranes or both (Augenstreich et al ., 2017; Augenstreich et al, 2019; Cambier et al, 2020; Osman et al ., 2020; Simeone et al ., 2021). In this work, we show that PDIM is essential for the mitochondrial damage and death in mTOR deficiency but whether this effect is solely by causing phagosomal damage or whether it additionally works with ESX-1/ESAT-6 to damage mitochondrial membranes remains a question.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that we only examined the early TLR2-dependent response. PDIM influences a variety of processes, including later TLR2-driven responses, phagosomal escape, and intracellular survival (Augenstreich et al, 2017;Barczak et al, 2017;Cambier et al, 2020;Hinman et al, 2021;Lerner et al, 2018;Osman et al, 2020;Quigley et al, 2017). It is possible that these processes are independent of preparation methods.…”
Section: Discussionmentioning
confidence: 99%
“…The outer membrane also contains a complex array of unique lipids, such as phthiocerol dimycocerosate (PDIM), phenolic glycolipids, and sulfolipids. Many of these lipids are bioactive; they can intercalate into host membranes, alter inflammatory signaling, disrupt phagosome maturation, and promote mycobacterial virulence (Cambier et al, 2020;Lerner et al, 2018;Quigley et al, 2017). Some outer membrane lipids, such as PDIM, phenolic glycolipids, and sulfoglycolipids, are thought to act as antagonists of pathogen recognition receptors (PRRs) or to shield underlying pathogen associated molecular patterns (PAMPs) to prevent them from activating PRRs (Blanc et al, 2017;Cambier et al, 2014;Reed et al, 2004).…”
Section: Introductionmentioning
confidence: 99%